Sistem Manajemen Keselamatan dan Kesehatan Kerja di PT Centex - Astuti, Rani Dwi; Purrohman, Purnama Syae (Utilitas, 2016)
This study aimed to determine how Occupational Safety and Health Management System in PT Century Textile Industry. The method used is the qualitative nature is descriptive. The number of informants of this research consists of as many as 3 Safety Coordinator PT Century Textile Industry, Safety Coordinator Dyeing Departement, and Safety Coordinator Weaving Departement, all their informants are people who know and hostage in order in the occupational safety and health management system. The research sampling using purposive sampling. Based on the findings, that occupational safety and health management system includes the planning or policy of occupational safety and health, the implementation or communication of occupational safety and health, and evaluation of occupational safety and health. Planning or policy of occupational safety and health is done through 3 aspects: regulation of occupational safety and health management system which must be obeyed by all employees, occupational safety and health Standard Operating Procedures (SOP), and maintenance of machinery and work equipment. In the implementation or communication of safety and health through 3 aspects is the socialization and dissemination of occupational safety and health information, internal communication conducted between employees both- superiors about occupational safety and health, and external communication to the community about K3. The last stage of occupational safety and health evaluation is the stage of measurement, assessment, and improvement that must be done in PT Century Textile Industry by holding a safety patrol program.